Pigmented free floating vitreous cyst in a 10 years old child - Majumder, Parthopratim Dutta; Ganesh, Nagalekshmi; Tomar, Vijay Pratap Singh; Kharel, Ranju; Sen, Parveen (Nepalese Journal of Ophthalmology, 2018)
Pigmented free-floating vitreous cyst in retrolental space is rare. It can represent its congenital origin after spontaneous detachment from the ciliary body epithelium or after trivial injury. We report a case of pigmented, free floating non-infective vitreous cyst in a 10 year old child who presented with compliant of transient blurring of vision three days after she joined swimming class. A thorough eye examination with ultrasound B scan and ultrasound biomicroscopy was done to rule out any other associated conditions.